الخط الكوفي: تطوره وخصائصه وأنواعه - Bousselam, Anass (Universitas Negeri Malang, 2023)
The article initially refers to the emergence of the Kufic script, then shows the development of this ancient type of calligraphy and then identifies its most prominent characteristics and reviews a group of its types. The article concludes its axes by identifying the most important rules for writing the Kufic script. يشير المقال - في البداية - إلى نشأة الخط الكوفي، ثم يبين تطور هذا النوع العريق من الخط، ويحدد - بعد ذلك – أبرز خصائصه، ويستعرض مجموعة من أنواعه، ويختم المقالُ محاورَه بتحديد أهم قواعد كتابة الخط الكوفي.